Study of Cholesterol Intake, Proportion of Fat in the Diet to Body Fat in Adolescents - Lourena, Crysty; Tamtomo, Didik Gunawan; Wiboworini, Budiyanti (Indonesian Journal of Global Health Research, 2024)
The increase of body fat over students is caused by changes in lifestyle, especially diet, where adolescents often consume high-energy foods sourced from fat. High consumption of saturated fats can increase cholesterol and inflammation in the body, leading to fat storage disorders. To prevent this increase in excess, it is necessary to increase the intake unsaturated fat, like MUFA and PUFA which are known as one of the anti-inflammatory substances that can reduce fat in the body. Therefore, when consuming fats, a larger proportion of PUFA and MUFA is needed compared to the proportion of saturated fats. Objective: To analyze the relationship between cholesterol intake and the proportion of fat intake with percent body fat. Method: This study used a cross-sectional design with multistage random sampling involving 161 adolescents aged 15-18 years who attended high schools and vocational schools in Surakarta. Food intake data was collected using food frequency questionnaire (SQFFQ). Percent body fat was measured using Bioelectrical Impendence Analysis (BIA) Omron HBF -375 Karada scan. Bivariate data analysis using spearman rank. Results: The results of the analysis showed no relationship between cholesterol intake and percent body fat (p=0.531), proportion of saturated fat (p=0.332), proportion of MUFA (p=0.269), proportion of PUFA (p=0.213) Conclusions: It can be concluded that cholesterol intake and proportion of saturated fat, PUFA, and MUFA are not associated with percent body fat.